Innovation histories: A method from learning from experience - and Douthwaite, B; Ashby, J (2005)
Preparing an ‘innovation history’ is a method for recording and reflecting on an innovation process. People who have been involved in the innovation jointly construct a detailed written account (sometimes referred to as a ‘learning history’) based on their recollections and on available documents. The process of preparing this history stimulates discussion, reflection and learning amongst stakeholders. Subsequent planning can build on the lessons learned, formulate a shared vision and act as a catalyst for change. Based on the initial detailed account of the innovation process, more concise informational products can be prepared that summarize the innovation process for wider dissemination of findings. These may include public awareness materials, policy briefs or articles in professional journals.